2017
DOI: 10.1152/ajpheart.00290.2017
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial function in engineered cardiac tissues is regulated by extracellular matrix elasticity and tissue alignment

Abstract: Mitochondria in cardiac myocytes are critical for generating ATP to meet the high metabolic demands associated with sarcomere shortening. Distinct remodeling of mitochondrial structure and function occur in cardiac myocytes in both developmental and pathological settings. However, the factors that underlie these changes are poorly understood. Because remodeling of tissue architecture and extracellular matrix (ECM) elasticity are also hallmarks of ventricular development and disease, we hypothesize that these e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 60 publications
5
39
0
Order By: Relevance
“…3C). The enrichment of these factors in adult CDMs is consistent with adult cardiac biology, which exhibits increased ECM crosslinking 56 and organization 23 and is associated with greater CM maturity 22,57 .…”
Section: Age-specific Cardiac Cdmssupporting
confidence: 63%
See 2 more Smart Citations
“…3C). The enrichment of these factors in adult CDMs is consistent with adult cardiac biology, which exhibits increased ECM crosslinking 56 and organization 23 and is associated with greater CM maturity 22,57 .…”
Section: Age-specific Cardiac Cdmssupporting
confidence: 63%
“…CM function is also strongly influenced by morphology 22 , with cells increasing in size as they mature, and high aspect-ratio CMs achieving the most efficient contractions 16 . CMs cultured on fetal CDMs exhibited greater than a two-fold increase in morphological aspect ratio than those cultured on Matrigel, and CMs on both fetal and adult CDMs adopted narrower cell widths than those on Matrigel (Fig.…”
Section: Ipsc-cm Response To Age-specific Cardiac Cdmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seahorse Bioscience XFe96 analyzer, as previously described 37 . Briefly, after cardiac function measurements (hemodynamic evaluation), heart tissue (400 mg) was harvested and homogenized in a prepared mitochondrial buffer (10 ml of 0.1 M Tris-MOPS and 1 ml of 0.1 M EGTA/Tris in 20 ml of 1 M sucrose).…”
Section: Determination Of Cardiac Function Myocardial Infarct Sizementioning
confidence: 99%
“…There is little data in the literature related to whether ECM stiffness affects mitochondrial structure and function. Recently, it was reported that in cardiac myocytes, baseline metabolism is influenced by ECM stiffness and, even more interestingly, the ability of cells to adapt to metabolic stress is regulated by both ECM stiffness and fiber alignment [ 92 ]. To complement these findings, below we present preliminary data that suggest a weak dependence of mitochondrial structure and function on ECM stiffness in VSMCs in culture, in qualitative agreement with the result in cardiac myocytes.…”
Section: Mechanobiology Of Mitochondrial Structure and Functionmentioning
confidence: 99%